The Role of the Minimum Wage in the Welfare State: An Appraisal - Juan F. Jimeno; Florentino Felgueroso; Juan José Dolado (Institute for the Study of Labor (IZA), 2000)
In order to offer a balanced assessment of the role of minimum wages in the Welfare State, seven basic questions need to be answered: (i) Why is the minimum wage a useful redistributive tool?; (ii) How binding are minimum wage floors in different countries?; (iii) To what extent do minimum wages have the adverse consequences that standard analysis predict?; (iv) Are there strong theoretical grounds underlying the revisionist results?; (v) Who supports minimum wages?; (vi) Under which conditions is the minimum wage a better tool than other policy instruments to achieve income redistribution?; and, finally, (vii) What is the overall cross-country time-series evidence regarding the employment effect of the minima? The aim of this paper is to provide an appraisal on the available evidence for each of the above-mentioned issues.
Keywords: J31; 330; Minimum wages; employment; inequality; Mindestlohn; Einkommensumverteilung; Beschäftigungseffekt; Theorie; OECD-Staaten